Comparing offline and online administrations of measures of truth effect, metacognitive awareness and working memory in Malaysia during the Movement Control Order (MCO) - Chan, Wai Mak; Weng-Tink, Chooi (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper described how the truth effect and its relationship with metacognitive awareness and working memory was converted from a physical (offline) administration to an online study due to COVID-19 pandemic-related lockdown measures. The truth effect refers to the tendency for repeated statements to be judged as more true than new statements. Processing fluency is the ease of mentally processing information. The automatic and unreflective mental system associated with processing fluency can be enhanced by repetition. Metacognitive awareness and working memory were conceptualized as a deliberate and analytical cognitive system in the current study. Fifteen offline participants and fifteen online participants were compared on measures of the truth effect, metacognitive awareness, and working memory. There were no significant differences between the offline and online groups in measures of metacognitive awareness, working memory, fluency and the truth effect, suggesting that the online administration of study measures was comparable to traditional methods of administration in a physical laboratory. Even with the small sample size, our findings suggested that statements that were presented more than once were rated significantly more true compared to new information. In conclusion, the truth effect was detected both in online and offline settings in our sample of Malaysian young adults. Our study documented how cognitive tasks can be administered in an online setting using a common teleconference application (i.e., Zoom). Our findings provide support and reference for researchers to conduct research online especially during times of restricted movements and the current climate of working and studying from home.